(untitled) (Journal of the College of Basic Education, 2022)
Traumatic crises are caused by severe, sudden and unexpected events, which lead to a major emotional shock that takes hold of the individual temporarily. Traumatic crises are a response to an event that threatens basic aspects of life. Crises may be traumatic for many reasons, such as the death of a loved one, illness or severe disability, dismissal from work or exposure to severe violence that may lead to psychological injury. In addition, accidents and disasters that affect large groups of individuals can lead to traumatic crises, Often, dealing with these crises and dealing with them is painful and requires a great effort. The research aimed to build a crisis scale, and the researcher followed the descriptive approach in the survey method to address the problem, and the research community consisted of (33) teaching staff. While the most important recommendations are the necessity of having a working team in the university and colleges trained on how to deal with crises.